The role of Sharia compliance in moderating the indirect influence of board diversity on roe mediated by Zakat disclosure - Firdaus, Rizalnur; Sumiati, Sumiati; Djazuli, Atim; Indrawati, Nur Khusniyah (Edelweiss Applied Science and Technology, 2024)
This study aims to examine the moderating role of Sharia compliance on the relationship between the diversity of the Board of Directors, Board of Commissioners, and Sharia Supervisory Board and Return on Equity (ROE), with Zakat Disclosure as a mediating factor. The research is grounded in agency theory, stakeholder theory, and legitimacy theory, focusing on how board diversity and Sharia compliance influence corporate governance and financial performance, specifically in the context of Islamic banking. The study utilizes a sample of Islamic commercial banks listed with Bank Indonesia. Data from the banks’ annual reports and financial statements between 2013 and 2023 are analyzed using a panel data regression model. Multi-Group Analysis (MGA) is employed to test the moderating effects of Sharia compliance on the indirect relationships between board diversity and ROE, mediated by zakat disclosure. The results show that Sharia compliance moderates the relationship between the diversity of the Board of Directors and ROE, with zakat disclosure acting as a mediator. However, Sharia compliance does not moderate the relationship between the diversity of the Board of Commissioners and Sharia Supervisory Board with ROE, as mediated by zakat disclosure. The research provides insights for Islamic banks, highlighting the importance of Sharia compliance and board diversity in enhancing financial performance through zakat disclosure. The findings can inform regulators and practitioners in improving corporate governance practices within Islamic financial institutions. This study contributes to the literature by offering new evidence on the role of Sharia compliance in the governance-performance relationship, particularly the indirect effects through zakat disclosure, and how this dynamic operates within the unique framework of Islamic banking.